The Impact of Intellectual Property Rights Enhancement on Corporate Resilience during Economic Crises - Minho Kim; Sang-Ok Choi (Journal of Intellectual Property, 2025)
This study analyzed the impact of intellectual property rights enhancement on changes in corporate sales and employment and business resilience during economic crises based on ”The Survey of Business Activities” data from 2018 to 2022. The results of the analysis using latent growth modeling revealed that an increase in intellectual property rights significantly improved the speed of recovery for corporate sales and employment, even during economic crises. In particular, considering the impact of economic shocks (e.g., COVID-19) on business management, intellectual property rights were confirmed to play a crucial role in strengthening corporate resilience. Companies with intellectual property rights demonstrated a faster and more effective recovery of sales and employment after the crisis, suggesting that intellectual property rights contribute to enhancing corporate stability and long-term growth potential. Similar trends were also observed in the analysis of small and medium-sized enterprises (SMEs). The results of this study showed that SMEs with increased intellectual property rights had significantly faster recovery rates in sales and employment, emphasizing the strategic importance of intellectual property rights enhancement in strengthening the resilience of SMEs. The study findings clearly identify the positive impact of intellectual property rights enhancement on corporate crisis responses and resilience improvement. They also suggest that policymakers must develop policies supporting the acquisition and utilization of intellectual property rights.